SOME NOTES ON LATGALIAN BOOKS IN THE MASSIVE UNION CATALOGUE „ANCIENT PRINTS IN LATVIAN 1525–1855” (1999) - Kalvāne, Skaidrīte (Via Latgalica, 2012)
Chronology of books published in Latgalian can be traced in bibliographical indexes of G. Manteuffel, V. Seile, J. Misiņš and fragmentarily in that of K. Estreicher. Latgalian publications have most broadly been reflected in the massive union catalogue of the National Library of Latvian „Ancient Prints in Latvian 1525–1855” (1999) – from the first known book of songs and prayers (1730) to „Gromotu dzismiu łacinsku” (1855). The massive union catalogue contains entries on 94 prints in Latgalian – existence of 8 of them is questioned or denied – 59 have been preserved to this day, 27 still remain unknown. Compilers of the catalogue have done a great job which deserves praise.Descriptions of prints use studies by literary historians which have not always been scientifically correct. Aim of the article – to attach importance to the need for and the chance to identify original sources of Latgalian prints and authors (localizers, translators) of spiritual literature.The article outlines the issue of authors of certain books, identifies the source of one book, points at certain little known fragmentary texts and handwritten books as well as the chance to search for and find new Latgalian publications today. It all clarifies the picture of Latgalian literature of the early period.In Poland several publications of small catechism in two languages – Polish-French – were known, by indication also of the author of the writing. It is possible to compare the Latgalian publication „Eysa sałasieyszona” with „Mały katechizm historyczny” published in 1819 in Wroclaw, just the text of Latgalian catechism is monolingual, resp. Latgalian.In Latgalian books usually their translators or authors are not specified. No matter how unusual it sounds, still it has not been demonstrated that Latgalian spiritual literature was only a translated literature, that there are no original writings.This time the notes on Latgalian books could end with an optimistic statement that still it is possible to find non-studied manuscripts prepared for publication. Striking evidence for that is text (sermons) book recently found in Alsunga, in the Alsunga church tower detected by the priest Andris Vasiļevskis.While in the Academic Library of the University of Latvia„Licieyba brolisties wyssu swatoku sirzu Jezu un Maryas. Pi Feymanu Baźnieycas” is still kept, not mentioned in the main catalogue and signed by the priest Jezups Macilevičs in 1853.„Gromota łyugszonu” published in 1820 is found in a book storage of Liepaja St. Joseph’s Catholic cathedral, which unlike the copy as described in the main catalogue (S: 1037), has remained much more complete, i. e. it has a cover page, the book has 385 pages in addition to the table of contents.